(untitled) (Aintelia Science Notes, 2022)
Conductive textiles play an important role in modern textile science as scientists are trying to integrate electronic devices into clothing for various purposes such as transmitting, tracking, and controlling movements. For this reason, researchers are trying to improve the conductivity of fabrics or yarns by using various materials and methods. In this study, the authors optimized conductive ink solution which is based on silver nanoparticles (AgNPs) known as electrically conductive which is applicable to traditional silk and wool textile products by printing and dyeing methods. With this application, the authors offered an innovative approach to the production of conductive textile surfaces. Several tests have been done to find out the change of conductivity and if those materials are applicable for our daily life usage. After applying AgNPs ink solution, the conductivity of silk (34.78 S/cm) is much higher than wool (25.28 S/cm) but after the color-fastness to rubbing test, wool’s (2.12 S/cm) conductivity is much higher than silk (1.01 S/cm). On the other hand, after the wash fastness test, the conductivity of wool decreased (5.43 S/cm). So, the authors have found that the conductive wool yarn is much more stable than silk yarn or fabric for daily life application.